Apples, tomatoes, and health: comparison of structural characteristics of the L1 and L2 mental lexicons - Agustín Llach, M.P. y Palapanidi, K. (Applied Psycholinguistics, 2024)
The present study delves into the structure and lexical organization of L1 and L2 mental lexicons. Indirect access to the mental lexicon is provided by semantic fluency tasks, which inform researchers about how the words are organized in the mental lexicon and retrieved when necessary. Here, two groups of participants were asked to retrieve as many words of the category fruits and vegetables as possible in two minutes. The first group is made up of native speakers of Spanish who responded in Spanish L1, whereas the second group is made up of native speakers of Greek who are learning Spanish foreign language (SFL) who responded first in Spanish FL and later in Greek L1. The three sets of responses were scrutinized and compared for similarities and differences. Results point to a retrieval mechanism based on L1-mediated access for SFL learners and slightly different structures of the mental lexicon. Even in very advanced learners, lexical organization and word retrieval in the FL resembles L1 organization.